THE IMPACT OF URBAN DYNAMIC TO LAND VALUE IN PERI-URBAN CORRIDORS OF SEMARANG, INDONESIA - Rakhmatulloh, Anita Ratnasari (Geoplanning: Journal of Geomatics and Planning, 2018)
Land use change will lead to the urban development dynamics beginning with physical changes, functional changes, spatial changes, socioeconomic changes, as well as demographic changes. Different land uses can offer different land rent or land values. Therefore, urban dynamic lead to the expansion of cityâs boundaries caused by land use change. The purpose of this study is to identify the level of change in the biased land value which is used to indicate the urban dynamics in corridor of Semarang-Ungaran and Semarang - Mranggen. This research method using GIS analysis to show the changes of land value. The result shows that the land value can be used to perceive the urban dynamics in both corridors.